2016
DOI: 10.1080/13543776.2016.1209488
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase inhibitors: an updated patent review (2012-2015)

Abstract: Two drugs, azacitidine and decitabine, have evidently shown efficacy in hematologic malignancies, yet do not work well on solid tumors, have low specificity, substantial toxicity, and poor bioavailability. With the rapid advancement in systems biology, drug combinations, such as DNMTi, in conjugation with histone deacetylase inhibitors (HDACi) or immunotherapy, probably serve as an efficient way of implementing epigenetic therapy. Meanwhile, the resolved autoinhibitory structures of DNMTs afford a novel strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 82 publications
1
37
0
1
Order By: Relevance
“…Several natural products, such as genistein, laccaic acid A, and (-)-epigallocatechin-3-O-gallate (EGCG), were reported to inhibits DNMT activity. Unfortunately, the potency of these compounds is lower than that of the nucleoside analogs and their in vivo inhibitory activity against solid tumors is rarely reported [60][61]. This situation prompts an urgent need to discover new-generation DNMT inhibitors with high in vitro and in vivo potency against tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several natural products, such as genistein, laccaic acid A, and (-)-epigallocatechin-3-O-gallate (EGCG), were reported to inhibits DNMT activity. Unfortunately, the potency of these compounds is lower than that of the nucleoside analogs and their in vivo inhibitory activity against solid tumors is rarely reported [60][61]. This situation prompts an urgent need to discover new-generation DNMT inhibitors with high in vitro and in vivo potency against tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside analogs based on epigenetic inhibitors 5-azacytidine and 5-aza-2′-dC are in Phase I-III clinical trials for many human diseases, and two DNMT inhibitors, azacytidine and decitabine, have shown efficacy and received FDA approval for the treatment of myelodysplastic syndrome but not solid tumors [31,32]. Nevertheless, some studies showed 5-aza-2′-dC decreased pancreatic cancer cell proliferation and induced cell cycle arrest in an in vitro model [33,34,35].…”
Section: Dna Methylationmentioning
confidence: 99%
“…AZA and DAC have evidently demonstrated efficacy in hematologic malignancies such as MDS, AML and CLL, however, the use of DNMTis in solid tumors seems limited because of the low specificity, substantial toxicity, and poor bioavailability [132]. Moreover, the solid tumors patients also have DNMTis associated toxicity issue.…”
Section: Toxicity Issue Associated With Dnmtismentioning
confidence: 99%